Common Cholinergic, Noradrenergic, and Serotonergic Drugs Do Not Block VNS-Mediated Plasticity - Morrison, Robert A.; Abe, Stephanie T.; Danaphongse, Tanya; Ezhil, Vikram; Somaney, Armaan; Adcock, Katherine S.; Rennaker, Robert L.; Kilgard, Michael P.; Hays, Seth A. (Frontiers in Neuroscience, 2022)
Vagus nerve stimulation (VNS) delivered during motor rehabilitation enhances recovery from a wide array of neurological injuries and was recently approved by the U.S. FDA for chronic stroke. The benefits of VNS result from precisely timed engagement of neuromodulatory networks during rehabilitative training, which promotes synaptic plasticity in networks activated by rehabilitation. Previous studies demonstrate that lesions that deplete these neuromodulatory networks block VNS-mediated plasticity and accompanying enhancement of recovery. There is a great deal of interest in determining whether commonly prescribed pharmacological interventions that influence these neuromodulatory networks would similarly impair VNS effects. Here, we sought to directly test the effects of three common pharmaceuticals at clinically relevant doses that target neuromodulatory pathways on VNS-mediated plasticity in rats. To do so, rats were trained on a behavioral task in which jaw movement during chewing was paired with VNS and received daily injections of either oxybutynin, a cholinergic antagonist, prazosin, an adrenergic antagonist, duloxetine, a serotonin-norepinephrine reuptake inhibitor, or saline. After the final behavioral session, intracortical microstimulation (ICMS) was used to evaluate reorganization of motor cortex representations, with area of cortex eliciting jaw movement as the primary outcome. In animals that received control saline injections, VNS paired with training significantly increased the movement representation of the jaw compared to naïve animals, consistent with previous studies. Similarly, none of the drugs tested blocked this VNS-dependent reorganization of motor cortex. The present results provide direct evidence that these common pharmaceuticals, when used at clinically relevant doses, are unlikely to adversely impact the efficacy of VNS therapy.